Alternative Clinical Practice During the COVID-19 Pandemic: A Qualitative Study of Nursing Students' Potential Loss of Experience - Bente Dale Malones MSc, RN; Marita Christina Susanne Melbye MSc, RN; Trude Fløystad Eines MSc, RN; Johanne Alteren PhD, CNSc, BSN, RN (SAGE Publishing, 2023)
Introduction During the COVID-19 pandemic, the lockdown of nursing institutions changed nursing students' learning conditions in clinical practice. They were removed from their ordinary clinical practice and isolated in their homes for one week before resuming an alternative clinical practice. Owing to the changed learning conditions, nursing students had to readjust and find new and different solutions to manage their own learning. Objectives This study aimed to investigate the impact of removing first-year nursing students from clinical practice during the COVID-19 pandemic on their perceived learning and development. Methods A qualitative descriptive and interpretative design based on group and individual interviews was used. Eleven first-year nursing students from a university college in Norway participated in the study. They were interviewed from their homes, after completing their first 10-week clinical practice. Three group interviews and two individual interviews were recorded using the digital live video aid Zoom and analyzed using systematic text condensation. Results The main theme "loss of experience," summarized how the nursing students experienced their first clinical practice during the COVID-19 lockdown. The nursing students shifted from a predictable to an unpredictable clinical practice without supervision from the nurse supervisor or the nurse educator. The organization and planning of the practice were left to the students, who bore the responsibility of achieving the learning outcomes. Three categories were identified: unpredictable learning situations, compensating learning activities, and achieving learning outcomes. Conclusions Nursing students faced difficulties in their first clinical practice during the COVID-19 lockdown, which made a challenging study situation. Too much autonomy and responsibility for their own learning reinforced a loss of experience. The uncertainty of the study situation potentially harmed their professional development, learning outcomes, and self-efficacy, especially concerning basic nursing skills.